2000
DOI: 10.1889/1.1833121
|View full text |Cite
|
Sign up to set email alerts
|

40.3L: Late‐News Paper: Color Changing Materials for OLED Microdisplays

Abstract: Various approaches to color changing media (CCM) for color microdisplays using blue pixelated OLED display with blue-togreen and blue-to-red CCM have been studied. Vacuum-deposited CCM films have been demonstrated with optical density 3.75/micron at the maximum of absorption and absolute quantum efficiency of photoluminescence of 82% and 67% for B/G and B/R CCM, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…For full-color active-matrix organic light-emitting diodes (AMOLEDs), the current color-patterning method of choice is the thermal evaporation of small-molecules through a fine metal shadow mask. Because this method is limited to small-sized substrates (≤730 × 460 mm 2 , currently), color-changing media (CCM), 1 laser-induced thermal imaging (LITI), 2 ink-jet printing, 3 and, more recently, laser-induced pattern-wise sublimation (LIPS) 4 were proposed for larger substrates. However, there is no commercial production of AMOLEDs using these technologies as of yet.…”
Section: Introductionmentioning
confidence: 99%
“…For full-color active-matrix organic light-emitting diodes (AMOLEDs), the current color-patterning method of choice is the thermal evaporation of small-molecules through a fine metal shadow mask. Because this method is limited to small-sized substrates (≤730 × 460 mm 2 , currently), color-changing media (CCM), 1 laser-induced thermal imaging (LITI), 2 ink-jet printing, 3 and, more recently, laser-induced pattern-wise sublimation (LIPS) 4 were proposed for larger substrates. However, there is no commercial production of AMOLEDs using these technologies as of yet.…”
Section: Introductionmentioning
confidence: 99%
“…Ghosh el al. tested color-changing materials (CCMs) for OLED microdisplays, as shown in Figure 5(a) [40]. They compared CCMs processed via spin-coating and vacuumdepositing and found that only vacuum-deposited films satisfied the requirements for OLED microdisplays.…”
Section: Color Conversion Structuresmentioning
confidence: 99%
“…Figure 5. (a) Cross-section of an OLED display sealed with the CCM/C/F substrate[40]. Reprinted with permission from ref [40]…”
mentioning
confidence: 99%
See 1 more Smart Citation